Recent Updates of Natural and Synthetic URAT1 Inhibitors and Novel Screening Methods - Ying Chen (Hindawi Limited, 2021)
Human urate anion transporter 1 (hURAT1) is responsible for the reabsorption of uric acid in the proximal renal tubules and is a promising therapeutic target for treating hyperuricemia. To mitigate the side effects of URAT1-targeted clinical agents such as benzbromarone, there is significant interest in discovering new URAT1 inhibitors and developing technology that can evaluate URAT1 inhibition. This review summarizes the methods for assay of URAT1 inhibition and the progress on the discovery of natural and synthetic URAT1 inhibitors in the past five years.